Development of a secure signature recognition system by using Matlab / Fauziyah Salehuddin - Salehuddin, Fauziyah (2001)
Signature is one of the most important personal identification methods. Its prevalent usage demands that security be provided to prevent forgery. The paper highlights the development of signature recognition system using MATLAB by comparing the input signature with the stored templates. A successful recognition system was developed.